Fireproof heat-insulating glass and preparation process thereof

By using double cross-linked gel monomers to prepare a fire-proof gel layer, and combining it with a heat-insulating film layer and a modified glass substrate to form a three-dimensional network structure, it solves the problem of delamination and peeling of existing fire-proof and heat-insulating glass during long-term use. problem, achieving higher stability and fire protection and thermal insulation performance.

CN119319703APending Publication Date: 2025-01-17SHANXI BAIAO INTELLIGENT GLASS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411692931.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

During long-term use, temperature changes or external force impact, existing fire-resistant and heat-insulating glass is prone to layering and peeling between multi-layer composite materials, reducing the fire-resistant and heat-insulating effect and affecting the overall performance and service life.

Method used

Double cross-linked gel monomer is used to prepare a fire-resistant gel layer, and is combined with a heat-insulating film layer and a modified glass substrate to form a three-dimensional network structure, enhance interface bonding, and improve stability and fire-proof and heat-insulating properties.

Benefits of technology

By forming a stable three-dimensional network structure, the stability and fire insulation performance of fire-resistant and insulating glass are improved, the fire-resistant time is extended, the heat conduction efficiency is reduced, and the overall performance and service life are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119319703A_ABST
    Figure CN119319703A_ABST
Patent Text Reader

Abstract

The invention relates to fireproof and heat-insulating glass and a preparation process thereof, and relates to the field of fireproof and heat-insulating materials, the fireproof and heat-insulating glass comprises a heat-insulating film layer I, a fireproof gel layer I, a glass substrate, a fireproof gel layer II and a heat-insulating film layer II, the fireproof gel layer I and the fireproof gel layer II are prepared by adopting a mixed gel solution, the mixed gel solution is prepared from the following raw materials in parts by mass: 80 to 100 parts of bi-crosslinking gel monomer, 5 to 10 parts of crosslinking agent, 20 to 30 parts of composite flame retardant and 1 to 3 parts of initiator. The preparation process comprises the following steps: preparing a mixed gel solution, preparing the fireproof gel layer I and the fireproof gel layer II on the surface of the glass substrate, hot-pressing and laminating the heat insulation film layer I to the surface of the fireproof gel layer I, and hot-pressing and laminating the heat insulation film layer II to the surface of the fireproof gel layer II to obtain the fireproof heat insulation glass. The fireproof and heat-insulating glass has the effect of improving the interlayer binding force of the fireproof and heat-insulating glass, the stability can be improved, and the fireproof and heat-insulating performance is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fireproof and heat-insulating materials, and in particular to a fireproof and heat-insulating glass and a preparation process thereof. Background Art

[0002] As an important building material, fireproof and heat-insulating glass has been widely used in modern buildings. It can not only effectively prevent the spread of fire, but also significantly improve the thermal insulation performance of buildings, thereby reducing energy consumption and improving living comfort. With the acceleration of urbanization, the demand for high-rise buildings and large public facilities is increasing, and the importance of fireproof and heat-insulating glass is becoming increasingly prominent.

[0003] At present, in order to achieve fireproof and heat-insulating functions, common technical means include using single-layer or multi-layer composite materials to enhance the fireproof and heat-insulating properties of glass. Due to the large differences in material properties and weak bonding strength, multi-layer composite materials are prone to delamination and peeling between layers when used for a long time, when the temperature changes or when subjected to external force, thereby reducing the fireproof and heat-insulating effects and affecting the overall performance and service life, so there is room for improvement. Summary of the invention

[0004] In order to improve the stability of fireproof and heat-insulating glass, the present application provides a fireproof and heat-insulating glass and a preparation process thereof.

[0005] The present application provides a fireproof heat-insulating glass and a preparation process thereof using the following technical solutions: In the first aspect, the present application provides a fireproof and heat-insulating glass, which adopts the following technical solution: A fireproof heat-insulating glass comprises a heat-insulating film layer I, a fireproof gel layer I, a glass substrate, a fireproof gel layer II and a heat-insulating film layer II. The fireproof gel layer I and the fireproof gel layer II are prepared by a mixed gel solution. The raw materials for preparing the mixed gel solution include the following components in parts by weight: Double cross-linked gel monomer 80-100 parts Crosslinking agent 5-10 parts Composite flame retardant 20-30 parts 1-3 parts of initiator.

[0006] The double-crosslinked gel monomer can form a three-dimensional network structure, which can make the gel structure more stable and tough, improve thermal stability, effectively block the spread of flames and heat transfer, extend the heat conduction path, limit gas convection, enhance the blocking effect of thermal radiation, reduce heat conduction efficiency, and improve thermal insulation and fire resistance. The composite flame retardant plays a synergistic role when heated, preventing the spread of flames by physical and chemical means, enhancing thermal insulation and flame retardant effects, and improving fire resistance and thermal insulation. The thermal insulation film layer can effectively block the transfer of heat, and its internal microstructure and molecular arrangement hinder heat from passing through the film, while The heat-insulating film layer has high reflectivity for infrared and other thermal radiation bands, and its high density can prevent the flow of air inside it, reduce heat convection, and in a fire scene, reduce the heat transfer from the flame side to the other side, reduce the temperature rise rate of the back-fire surface, provide efficient heat-insulating protection for the fire-proof heat-insulating glass, and work together with the three-dimensional network structure and composite flame retardant in the fire-proof gel layer to reduce heat conduction and effectively improve the fire-proof and heat-insulating performance. The gel obtained by double cross-linking has rich functional groups, which can enhance the interface bonding strength, thereby improving the bonding strength with the glass substrate and the heat-insulating film layer, and improving the stability of the fire-proof and heat-insulating glass, thereby improving the fire-proof and heat-insulating performance.

[0007] Preferably, the double cross-linked gel monomer comprises sodium silicate, hydroxyethyl acrylate and N-hydroxymethyl acrylamide.

[0008] Sodium silicate gel is a silicate that can be generated at high temperature and has good flame retardant effect. The groups of hydroxyethyl acrylate and N-hydroxymethyl acrylamide can interact with it to promote the formation of stable carbon layer and thermal insulation layer, prolong the fire resistance time and improve its fireproof performance. Sodium silicate gel can be dehydrated to form a porous structure for thermal insulation in a high temperature environment. The gel structure formed by hydroxyethyl acrylate and N-hydroxymethyl acrylamide has low thermal conductivity. By increasing the length of the heat transfer path through double cross-linking, it can effectively reduce the temperature rise rate and improve the thermal insulation performance. The silicate groups generated after the hydrolysis of sodium silicate can form chemical bonds or physical adsorption with the silicon hydroxyl groups on the surface of the glass. The hydroxyl and ester groups in hydroxyethyl acrylate and N-hydroxymethyl acrylamide can form chemical bonds or physical adsorption with the silicon hydroxyl groups on the surface of the glass. Functional groups such as hydroxymethyl and amide in methacrylamide can react chemically with active groups on the surface of the glass substrate and the thermal insulation film layer, such as hydrogen bonding or forming covalent bonds, to enhance the connection with the glass, and these functional groups participate in cross-linking reactions during the gelation process to form a three-dimensional network structure. This three-dimensional network can better fit the microscopic morphology of the glass surface, penetrate into its pores and depressions, and increase the contact area; at the same time, the three-dimensional network structure enhances the cohesive strength and flexibility of the gel, so that when the gel faces stress caused by temperature changes, it can disperse the stress through its own deformation, avoid interfacial peeling caused by stress concentration, and effectively improve the adhesion of the gel to the glass substrate and the thermal insulation film layer.

[0009] Preferably, the mass ratio of the sodium silicate, hydroxyethyl acrylate and N-hydroxymethyl acrylamide is 1:0.5:(0.17-0.65).

[0010] The fireproof gel layer prepared according to the above ratio has good adhesion properties and can effectively improve the fireproof performance and heat insulation performance.

[0011] Preferably, the cross-linking agent comprises diethylenetriamine and aluminum chloride.

[0012] Diethylenetriamine contains amino groups and has high reactivity. It can react with functional groups such as carboxyl and hydroxyl in the gel system. Aluminum chloride provides aluminum ions in the solution, and aluminum ions can react with silicate ions, carboxyl groups, etc. in the system by coordination cross-linking reaction. When the two act together as cross-linking agents, they can make the double cross-linked gel monomer form a more stable and uniform three-dimensional network structure. This structure can better fill and fit the microscopic pores and depressions on the surface of the material, forming a strong connection, and enhancing the adhesion of the gel to the glass substrate and the thermal insulation film layer; at the same time, the stable three-dimensional network structure improves the cohesive strength of the gel, making it less likely to be destroyed when facing external forces, temperature changes, etc., thereby improving the stability of the fire-resistant and heat-insulating glass during long-term use; the structure can effectively block the spread of flames, maintain the integrity of the gel at high temperatures, prevent it from breaking or decomposing, extend the heat conduction path, limit gas convection, and enhance the barrier effect to thermal radiation, thereby improving the fireproof and heat-insulating properties.

[0013] Preferably, the raw materials for preparing the composite flame retardant include nano silicon dioxide and melamine polyphosphate.

[0014] Nano-silicon dioxide has a high specific surface area and nano-size effect. During the combustion process, it can form a physical barrier layer on the surface of the material to prevent heat and oxygen from transferring to the inside. When heated, melamine polyphosphate decomposes to produce non-combustible gas, which can dilute the oxygen concentration in the surrounding environment, inhibit the intensity of the combustion reaction, and promote the formation of a carbonized layer. The two work synergistically, and the carbonized layer cooperates with the barrier layer of nano-silicon dioxide to further enhance the barrier effect against heat and oxygen, effectively improve the fireproof and heat-insulating properties of fire-resistant and heat-insulating glass, prevent the spread of flames, and significantly reduce the transfer of heat.

[0015] Preferably, the mass ratio of the nano-silicon dioxide to melamine polyphosphate is 1:(1.6-2).

[0016] The composite flame retardant prepared according to the above mass ratio has a good synergistic effect and can effectively improve the fireproof and heat-insulating properties.

[0017] Preferably, the composite flame retardant is prepared by the following steps: Nano silicon dioxide is dispersed in N, N-dimethylformamide, and a nano silicon dioxide dispersion is obtained after ultrasonic treatment; melamine polyphosphate is added to the nano silicon dioxide dispersion, heated and stirred for reaction, and the solvent is removed by reduced pressure distillation to obtain a composite flame retardant.

[0018] The composite flame retardant prepared according to the above steps has good dispersibility, and the nano silicon dioxide and melamine polyphosphate have a good synergistic effect, which can effectively improve the fireproofing and heat insulation properties of the composite flame retardant.

[0019] Preferably, the glass substrate is subjected to modification treatment to obtain a modified glass substrate, and the modified glass substrate is prepared by the following steps: The glass substrate is ultrasonically washed in ethanol and vacuum dried to obtain a pre-treated glass substrate; the pre-treated glass substrate is bombarded with plasma to obtain a preliminary treated substrate; the preliminary treated substrate is immersed in a silane coupling agent ethanol solution, the pH is adjusted to acidic with hydrochloric acid, the treated glass substrate is taken out after immersion, and the modified glass substrate is obtained after drying.

[0020] The pretreatment step can make the surface of the glass substrate clean and dry, providing a good foundation for subsequent treatment; the glass substrate pretreated by plasma bombardment can produce more active sites on the glass surface, thereby improving the bonding ability between the glass substrate and the fireproof gel layer; the silanol generated by the hydrolysis of the silane coupling agent and the active groups such as hydroxyl groups generated by the plasma bombardment of the preliminary treated substrate undergo condensation reaction to form a strong chemical bond, and the other end of the silane coupling agent can interact with the functional groups in the fireproof gel layer, thereby bridging the glass substrate and the fireproof gel layer, enhancing the adhesion between the two, and improving the stability of the fireproof and heat-insulating glass, thereby improving the fireproof and heat-insulating properties.

[0021] Preferably, the thermal insulation film layer is subjected to a modification treatment to obtain a modified thermal insulation film layer, and the raw materials for preparing the modified thermal insulation film layer include a thermal insulation film layer body and dopamine.

[0022] The thermal insulation film layer is modified with dopamine, which effectively improves the adhesion performance. Dopamine has a catechol structure and can self-polymerize to form a polydopamine coating. The polydopamine coating can tightly adhere to the surface of the thermal insulation film layer to form a solid underlying structure. At the same time, polydopamine is rich in active functional groups such as amino groups and hydroxyls, and can hydrogen bond or chemically react with functional groups such as carboxyl and hydroxyl groups in the fireproof gel layer to improve the adhesion of the two, effectively reduce the stratification phenomenon caused by various external forces, temperature changes and other factors during use, and improve the stability of the fireproof and heat-insulating glass, thereby improving its fire resistance and thermal insulation properties.

[0023] In a second aspect, the present application provides a process for preparing fireproof and heat-insulating glass, which adopts the following technical solution: A preparation process of fireproof and heat-insulating glass comprises the following steps: The double cross-linked gel monomer is dispersed in water and stirred until completely dissolved to obtain a double cross-linked monomer mixed solution; the cross-linking agent is dispersed in water and stirred until completely dissolved to obtain a cross-linking agent solution; the cross-linking agent solution is added to the double cross-linked monomer mixed solution, stirred for reaction, and then a mixed solution is obtained; the composite flame retardant is added to the mixed solution, stirred, and then an initiator is added, and then stirred to obtain a mixed gel solution; the glass substrate is immersed in the mixed gel solution, taken out after immersion, and after drying and curing, a glass substrate having a fireproof gel layer I and a fireproof gel layer II on both sides is obtained, and the heat insulation film layer I is hot-pressed and bonded to the surface of the fireproof gel layer I, and the heat insulation film layer II is hot-pressed and bonded to the surface of the fireproof gel layer II to obtain a fireproof heat-insulating glass.

[0024] The fireproof and heat-insulating glass prepared according to the above steps has good fireproof and heat-insulating properties, strong bonding between layers and good stability.

[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. Double cross-linked gel monomers can form a three-dimensional network structure, which can make the gel structure more stable and tough, improve thermal stability, effectively block the spread of flames and heat transfer, extend the heat conduction path, limit gas convection, enhance the blocking effect of thermal radiation, reduce heat conduction efficiency, and improve thermal insulation and fire resistance. The composite flame retardant plays a synergistic role when heated, preventing the spread of flames by physical and chemical means, enhancing thermal insulation and flame retardant effects, and improving fire resistance and thermal insulation. The thermal insulation film layer can effectively block the transfer of heat, and its internal microstructure and molecular arrangement hinder heat from passing through the film. At the same time, the thermal insulation film layer has high reflectivity for infrared and other thermal radiation bands, and its high density can prevent the flow of air inside it and reduce heat convection. In a fire scene, it reduces the heat transfer from the flame side to the other side, reduces the temperature rise rate of the back-fire surface, and provides efficient thermal insulation protection for the fireproof and heat-insulating glass. It works together with the three-dimensional network structure and composite flame retardant in the fireproof gel layer to reduce heat conduction and effectively improve the fireproof and heat-insulating properties. The gel obtained by double cross-linking has rich functional groups, which can enhance the interfacial bonding strength, thereby improving the bonding strength with the glass substrate and the thermal insulation film layer, and improving the stability of the fireproof and heat-insulating glass, thereby improving the fireproof and heat-insulating properties.

[0026] 2. Sodium silicate gel is a silicate that can be generated at high temperature and has good flame retardant effect. The groups of hydroxyethyl acrylate and N-hydroxymethyl acrylamide can interact with it to promote the formation of stable carbon layer and thermal insulation layer, prolong the fire resistance time and improve its fireproof performance; Sodium silicate gel can be dehydrated to form a porous structure for thermal insulation in a high temperature environment. The gel structure formed by hydroxyethyl acrylate and N-hydroxymethyl acrylamide has low thermal conductivity. By increasing the length of the heat transfer path through double cross-linking, the temperature rise rate can be effectively reduced and the thermal insulation performance can be improved; The silicate groups generated after the hydrolysis of sodium silicate can form chemical bonds or physical adsorption with the silicon hydroxyl groups on the glass surface. The hydroxyl and ester groups in hydroxyethyl acrylate and N- Functional groups such as hydroxymethyl and amide in hydroxymethyl acrylamide can react chemically with active groups on the surface of the glass substrate and the thermal insulation film layer, such as hydrogen bonding or forming covalent bonds, to enhance the connection with the glass, and these functional groups participate in cross-linking reactions during the gelation process to form a three-dimensional network structure. This three-dimensional network can better fit the microscopic morphology of the glass surface, penetrate into its pores and depressions, and increase the contact area; at the same time, the three-dimensional network structure enhances the cohesive strength and flexibility of the gel, so that when the gel faces stress caused by temperature changes, it can disperse the stress through its own deformation, avoid interfacial peeling caused by stress concentration, and effectively improve the adhesion of the gel to the glass substrate and the thermal insulation film layer.

[0027] 3. Diethylenetriamine contains amino groups and has high reactivity. It can react with functional groups such as carboxyl and hydroxyl in the gel system. Aluminum chloride provides aluminum ions in the solution. Aluminum ions can react with silicate ions, carboxyl groups, etc. in the system by coordination cross-linking reaction. When the two act together as cross-linking agents, they can make the double cross-linked gel monomer form a more stable and uniform three-dimensional network structure. This structure can better fill and fit the microscopic pores and depressions on the surface of the material, forming a strong connection, and enhancing the adhesion of the gel to the glass substrate and the thermal insulation film layer; at the same time, the stable three-dimensional network structure improves the cohesive strength of the gel, making it less likely to be destroyed in the face of external forces, temperature changes, etc., thereby improving the stability of the fire-proof and heat-insulating glass during long-term use; the structure can effectively block the spread of flames, maintain the integrity of the gel at high temperatures, prevent it from breaking or decomposing, extend the heat conduction path, limit gas convection, and enhance the barrier effect to thermal radiation, thereby improving the fireproof and heat-insulating properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a cross-sectional view of a fireproof and heat-insulating glass in an embodiment of the present application.

[0029] Explanation of the accompanying drawings: 1. Thermal insulation film layer I; 2. Fireproof gel layer I; 3. Glass substrate; 4. Fireproof gel layer II; 5. Thermal insulation film layer II. DETAILED DESCRIPTION

[0030] The present application discloses a fireproof heat-insulating glass and a preparation process thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments: Description of raw materials: Silane coupling agent is KH-550 (CAS No.: 919-30-2), dopamine hydrochloride (CAS No.: 62-31-7), nano-silica particle size is 30nm, purchased from Hangzhou Jikang New Materials Co., Ltd., melamine polyphosphate (CAS No.: 15541-60-3), sodium silicate (CAS No.: 1344-09-8), hydroxyethyl acrylate (CAS No.: 818-61-1), N-hydroxymethyl acrylamide (CAS No.: 924-42-5), diethylenetriamine (CAS No.: 111-40-0), the thermal insulation film layer is the industrial plant glass thermal insulation film of Hebei Hongchangsheng Environmental Protection Technology Co., Ltd.

[0031] Preparation Example 1 Preparation of modified glass substrate The glass substrate was ultrasonically washed in ethanol for 20 minutes, and vacuum dried at 60°C to obtain a pretreated glass substrate; the pretreated glass substrate was bombarded with plasma to obtain a preliminary treated substrate; the preliminary treated substrate was immersed in a silane coupling agent ethanol solution with a volume content of 5% and a solid-liquid ratio of 1:10 (g / mL), and the pH was adjusted to 4 with hydrochloric acid. After immersion for 10 minutes, the treated glass substrate was taken out and dried to obtain a modified glass substrate.

[0032] Preparation Example 2 Preparation of modified thermal insulation film layer Dopamine hydrochloride was dissolved in Tris-HCl buffer (pH 8) to make the concentration of the dopamine hydrochloride solution 2 g / L, the thermal insulation film layer was placed in the dopamine hydrochloride solution, reacted at 40° C. for 10 h, taken out, washed with deionized water, and dried after absorbing moisture with filter paper to obtain a modified thermal insulation film layer.

[0033] Example 1 Preparation of composite flame retardant 19.23 kg of nano-silica was dispersed in 100 L of N, N-dimethylformamide, and the nano-silica dispersion was obtained after ultrasonic treatment for 30 minutes. 30.77 kg of melamine polyphosphate was added to the nano-silica dispersion, and the mixture was stirred at 80° C. and 300 rpm for 4 hours. The solvent was removed by distillation under reduced pressure to obtain a composite flame retardant.

[0034] Preparation of fireproof and heat-insulating glass 80 kg of double cross-linked gel monomer was dispersed into 200 L of deionized water, wherein the mass ratio of sodium silicate, hydroxyethyl acrylate and N-hydroxymethyl acrylamide in the double cross-linked gel monomer was 1:0.5:0.17, and the mixture was stirred at a speed of 400 rpm until it was completely dissolved to obtain a double cross-linked monomer mixed solution; 5 kg of cross-linking agent was dispersed into 20 L of deionized water, wherein the mass ratio of diethylenetriamine and aluminum chloride in the cross-linking agent was 1:0.8, and the mixture was stirred at a speed of 200 rpm until it was completely dissolved to obtain a cross-linking agent solution; the cross-linking agent solution was added to the double cross-linked monomer mixed solution, and the mixture was stirred at a speed of 400 rpm. The mixture was stirred for 1 hour to obtain a mixed solution; 20 kg of the composite flame retardant was added to the mixed solution, and the mixture was stirred at a speed of 500 rpm for 1 hour; 1 kg of the initiator was added, and the mixture was stirred at a speed of 500 rpm for 15 minutes to obtain a mixed gel solution; a glass substrate was immersed in the mixed gel solution, and taken out after immersion for 1 hour. After drying and curing, a glass substrate having a fireproof gel layer I and a fireproof gel layer II on both sides was obtained, and the heat insulation film layer I was hot-pressed and bonded to the surface of the fireproof gel layer I, and the heat insulation film layer II was hot-pressed and bonded to the surface of the fireproof gel layer II to obtain a fireproof and heat-insulating glass.

[0035] Example 2 Preparation of composite flame retardant 16.67 kg of nano-silica was dispersed in 100 L of N, N-dimethylformamide, and the nano-silica dispersion was obtained after ultrasonic treatment for 30 minutes. 33.33 kg of melamine polyphosphate was added to the nano-silica dispersion, and the mixture was stirred at 80° C. and 300 rpm for 4 hours. The solvent was removed by distillation under reduced pressure to obtain a composite flame retardant.

[0036] Preparation of fireproof and heat-insulating glass 100 kg of double cross-linked gel monomer was dispersed into 200 L of deionized water, wherein the mass ratio of sodium silicate, hydroxyethyl acrylate and N-hydroxymethyl acrylamide in the double cross-linked gel monomer was 1:0.5:0.65, and the mixture was stirred at a speed of 400 rpm until it was completely dissolved to obtain a double cross-linked monomer mixed solution; 10 kg of cross-linking agent was dispersed into 20 L of deionized water, wherein the mass ratio of diethylenetriamine and aluminum chloride in the cross-linking agent was 1:0.8, and the mixture was stirred at a speed of 200 rpm until it was completely dissolved to obtain a cross-linking agent solution; the cross-linking agent solution was added to the double cross-linked monomer mixed solution, and the mixture was stirred at a speed of 400 rpm. The reaction was stirred for 1 hour to obtain a mixed solution; 30 kg of the composite flame retardant was added to the mixed solution, and the mixture was stirred at a speed of 500 rpm for 1 hour; 3 kg of the initiator was added, and the mixture was stirred at a speed of 500 rpm for 15 minutes to obtain a mixed gel solution; a glass substrate was immersed in the mixed gel solution, and taken out after immersion for 1 hour; after drying and curing, a glass substrate having a fireproof gel layer I and a fireproof gel layer II on both sides was obtained, respectively; the heat insulation film layer I was hot-pressed and bonded to the surface of the fireproof gel layer I, and the heat insulation film layer II was hot-pressed and bonded to the surface of the fireproof gel layer II to obtain a fireproof and heat-insulating glass.

[0037] Example 3 17.86 kg of nano-silica was dispersed in 100 L of N, N-dimethylformamide, and the nano-silica dispersion was obtained after ultrasonic treatment for 30 minutes. 32.14 kg of melamine polyphosphate was added to the nano-silica dispersion, and the mixture was stirred at 80° C. and 300 rpm for 4 hours. The solvent was removed by distillation under reduced pressure to obtain a composite flame retardant.

[0038] Preparation of fireproof and heat-insulating glass 90 kg of double cross-linked gel monomer was dispersed into 200 L of deionized water, wherein the mass ratio of sodium silicate, hydroxyethyl acrylate and N-hydroxymethyl acrylamide in the double cross-linked gel monomer was 1:0.5:0.41, and the mixture was stirred at a speed of 400 rpm until it was completely dissolved to obtain a double cross-linked monomer mixed solution; 7.5 kg of cross-linking agent was dispersed into 20 L of deionized water, wherein the mass ratio of diethylenetriamine and aluminum chloride in the cross-linking agent was 1:0.8, and the mixture was stirred at a speed of 200 rpm until it was completely dissolved to obtain a cross-linking agent solution; the cross-linking agent solution was added to the double cross-linked monomer mixed solution, and the mixture was stirred at a speed of 400 rpm. The reaction was stirred for 1 hour to obtain a mixed solution; 25 kg of the composite flame retardant was added to the mixed solution, and the mixture was stirred at a speed of 500 rpm for 1 hour; 2 kg of the initiator was added, and the mixture was stirred at a speed of 500 rpm for 15 minutes to obtain a mixed gel solution; a glass substrate was immersed in the mixed gel solution, and taken out after immersion for 1 hour; after drying and curing, a glass substrate having a fireproof gel layer I and a fireproof gel layer II on both sides was obtained, respectively; the heat insulation film layer I was hot-pressed and bonded to the surface of the fireproof gel layer I, and the heat insulation film layer II was hot-pressed and bonded to the surface of the fireproof gel layer II to obtain a fireproof and heat-insulating glass.

[0039] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that the mass ratio of sodium silicate, hydroxyethyl acrylate and N-hydroxymethyl acrylamide in the double cross-linked gel monomer in Example 4 is 1:0.5:0.1.

[0040] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that the mass ratio of sodium silicate, hydroxyethyl acrylate and N-hydroxymethyl acrylamide in the double cross-linked gel monomer in Example 5 is 1:0.5:0.8.

[0041] Example 6 Example 6 is based on Example 3, and the only difference between Example 6 and Example 3 is that in Example 6, no aluminum chloride is added as the cross-linking agent.

[0042] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the amount of nano-silicon dioxide in the composite flame retardant is 25 kg, and the amount of melamine polyphosphate is 25 kg.

[0043] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, the amount of nano-silicon dioxide in the composite flame retardant is 12.5 kg, and the amount of melamine polyphosphate is 37.5 kg.

[0044] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that melamine polyphosphate is not added to the composite flame retardant in Example 9.

[0045] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, the glass substrate is replaced by the modified glass substrate prepared in Preparation Example 1.

[0046] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that in Example 11, the thermal insulation film layer is replaced by the modified thermal insulation film layer prepared in Preparation Example 2.

[0047] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the double cross-linked gel monomer is replaced by sodium silicate.

[0048] Performance testing (1) GB / T2680-2021 Determination of visible light transmittance, direct solar transmittance, total solar transmittance, ultraviolet transmittance and related window glass parameters of architectural glass was selected as the standard to test the transmittance of the sample. Each sample was tested three times, and the average value was taken after measurement. The results are recorded in Table 1.

[0049] (2) Select "GB / T12513-2006 Fire resistance test method for glass-enclosed components" as the standard, conduct fire resistance performance tests on the samples, and test the fire protection time of the samples. Prepare three samples for each sample, take the average value after measurement, and record the results in Table 1.

[0050] (3) Select "GB / T13475-2008 Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Guarded Hot Plate Method" as the standard to test the thermal conductivity of the sample. Each sample is tested three times, and the average value is taken after measurement. The results are recorded in Table 1.

[0051] Table 1 Test results of light transmittance, fire resistance and thermal insulation performance of fireproof and heat-insulating glass Test results Light transmittance (%) Fire protection time (min) Thermal conductivity (W / (m·K)) Example 1 78.9 190±5 0.26 Example 2 79.1 190±5 0.24 Example 3 79.1 190±5 0.23 Example 4 80.5 180±5 0.35 Example 5 76.3 185±5 0.32 Example 6 79.8 185±5 0.29 Example 7 79.3 180±5 0.34 Example 8 76.8 190±5 0.22 Example 9 80.1 170±5 0.38 Example 10 77.6 200±5 0.19 Embodiment 11 77.4 195±5 0.21 Comparative Example 1 84.7 135±5 0.69 It can be seen from Table 1 that the light transmittance of Examples 1-3 is greater than 78.9%, the fire protection time is 190±5min, and the thermal conductivity is less than 0.26W / (m·K). It can be seen that the fire-resistant and heat-insulating glass prepared in the present application has good light transmittance, fire resistance and heat insulation performance, good interlayer bonding and stable performance.

[0052] As can be seen from Table 1, the only difference between Examples 4 and 5 and Example 3 is that the mass ratio of sodium silicate, hydroxyethyl acrylate and N-hydroxymethyl acrylamide in the double cross-linked gel monomer in Example 4 is 1:0.5:0.1, and the mass ratio of sodium silicate, hydroxyethyl acrylate and N-hydroxymethyl acrylamide in the double cross-linked gel monomer in Example 5 is 1:0.5:0.8. Compared with Example 3, the fire resistance and thermal insulation properties of Examples 4 and 5 are reduced; this is because the ratio of the components in the double cross-linked gel monomer is changed, too much N-hydroxymethyl acrylamide will make the gel hard, affect the transmittance, and easily generate internal stress; too little N-hydroxymethyl acrylamide will reduce the stability of the gel network, and the compatibility with the glass substrate and the thermal insulation film layer will deteriorate, thereby reducing the fire resistance and thermal insulation properties.

[0053] It can be seen from Table 1 that the only difference between Example 6 and Example 3 is that aluminum chloride is not added as the cross-linking agent in Example 6. Compared with Example 3, the fire resistance and thermal insulation properties of Example 6 are reduced. This is because without the addition of aluminum chloride, diethylenetriamine lacks a synergistic effect, the cohesive strength and stability of the gel network are reduced, and thus the fire resistance and thermal insulation properties are reduced.

[0054] As can be seen from Table 1, the only difference between Examples 7, 8, and 9 and Example 3 is that the mass ratio of nano-silicon dioxide and melamine polyphosphate in Example 7 is 1:1, the mass ratio of nano-silicon dioxide and melamine polyphosphate in Example 8 is 1:3, and melamine polyphosphate is not added to the composite flame retardant in Example 9. Compared with Example 3, the fire resistance and thermal insulation properties of Examples 7, 8, and 9 are reduced; this is because the ratio of nano-silicon dioxide and melamine polyphosphate is changed. Too little melamine polyphosphate will affect the flame retardant and thermal insulation effects, and too much melamine polyphosphate will not significantly improve the flame retardant and thermal insulation properties, but will affect the stability and light transmittance of the fireproof and thermal insulation glass, and the performance will be reduced after the ratio is destroyed; not adding melamine polyphosphate will lead to a further reduction in fireproof and thermal insulation properties.

[0055] It can be seen from Table 1 that the only difference between Example 10 and Example 3 is that the glass substrate in Example 10 is replaced with a modified glass substrate. Compared with Example 3, the fire resistance and heat insulation performance of Example 10 are improved; this is because the modification of the glass substrate can improve the adhesion between the glass substrate and the fireproof gel layer, thereby increasing the stability of the fireproof and heat-insulating glass and improving the fireproof and heat-insulating performance.

[0056] It can be seen from Table 1 that the only difference between Example 11 and Example 3 is that in Example 11, the thermal insulation film layer is replaced by a modified thermal insulation film layer. Compared with Example 3, the fireproof performance and thermal insulation performance of Example 11 are improved; this is because the thermal insulation film layer is modified to improve the adhesion between the thermal insulation film layer and the fireproof gel layer, thereby increasing the stability of the fireproof and heat-insulating glass and improving the fireproof and heat-insulating performance.

[0057] It can be seen from Table 1 that the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the double cross-linked gel monomer is replaced with sodium silicate. Compared with Example 3, the fireproof and heat-insulating properties of Comparative Example 1 are greatly reduced; this is because the double cross-linked gel network is replaced with sodium silicate gel, and the cohesive strength and stability of the gel network are reduced due to the lack of composite cross-linking treatment, thereby greatly reducing the fireproof and heat-insulating properties.

[0058] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A fireproof and heat-insulating glass, characterized in that: The invention comprises a heat-insulating film layer I, a fireproof gel layer I, a glass substrate, a fireproof gel layer II and a heat-insulating film layer II. The fireproof gel layer I and the fireproof gel layer II are prepared by a mixed gel solution. The raw materials for preparing the mixed gel solution include the following components in parts by weight: Double cross-linked gel monomer 80-100 parts Crosslinking agent 5-10 parts Composite flame retardant 20-30 parts 1-3 parts of initiator.

2. The fireproof and heat-insulating glass according to claim 1, characterized in that: The double cross-linked gel monomer includes sodium silicate, hydroxyethyl acrylate and N-hydroxymethyl acrylamide.

3. The fireproof and heat-insulating glass according to claim 2, characterized in that: The mass ratio of the sodium silicate, hydroxyethyl acrylate and N-hydroxymethyl acrylamide is 1:0.5:(0.17-0.65).

4. The fireproof and heat-insulating glass according to claim 1, characterized in that: The crosslinking agents include diethylenetriamine and aluminum chloride.

5. The fireproof and heat-insulating glass according to claim 1, characterized in that: The raw materials for preparing the composite flame retardant include nano silicon dioxide and melamine polyphosphate.

6. The fireproof and heat-insulating glass according to claim 5, characterized in that: The mass ratio of the nano silicon dioxide to melamine polyphosphate is 1:(1.6-2).

7. The fireproof and heat-insulating glass according to claim 6, characterized in that: The composite flame retardant is prepared by the following steps: Nano silicon dioxide is dispersed in N, N-dimethylformamide, and a nano silicon dioxide dispersion is obtained after ultrasonic treatment; melamine polyphosphate is added to the nano silicon dioxide dispersion, heated and stirred for reaction, and the solvent is removed by reduced pressure distillation to obtain a composite flame retardant.

8. The fireproof and heat-insulating glass according to claim 1, characterized in that: The glass substrate is subjected to modification treatment to obtain a modified glass substrate, and the modified glass substrate is prepared by the following steps: The glass substrate is ultrasonically washed in ethanol and vacuum dried to obtain a pre-treated glass substrate; the pre-treated glass substrate is bombarded with plasma to obtain a preliminary treated substrate; the preliminary treated substrate is immersed in a silane coupling agent ethanol solution, the pH is adjusted to acidic with hydrochloric acid, the treated glass substrate is taken out after immersion, and the modified glass substrate is obtained after drying.

9. The fireproof and heat-insulating glass according to claim 1, characterized in that: The thermal insulation film layer is subjected to modification treatment to obtain a modified thermal insulation film layer, and the raw materials for preparing the modified thermal insulation film layer include a thermal insulation film layer body and dopamine.

10. A process for preparing the fireproof and heat-insulating glass according to any one of claims 1 to 9, characterized in that: The following steps are involved: The double cross-linked gel monomer is dispersed in water and stirred until completely dissolved to obtain a double cross-linked monomer mixed liquid; the cross-linking agent is dispersed in water and stirred until completely dissolved to obtain a cross-linking agent solution; the cross-linking agent solution is added to the double cross-linked monomer mixed liquid, stirred for reaction, and then a mixed solution is obtained; the composite flame retardant is added to the mixed solution, and an initiator is added after stirring to obtain a mixed gel solution after stirring; a glass substrate is immersed in the mixed gel solution, taken out after immersion, and after drying and curing, a glass substrate having a fireproof gel layer I and a fireproof gel layer II on both sides is obtained, and the heat insulation film layer I is hot-pressed and bonded to the surface of the fireproof gel layer I, and the heat insulation film layer II is hot-pressed and bonded to the surface of the fireproof gel layer II to obtain a fireproof heat-insulating glass.

Citation Information

Cited By

  • Composite isolation fireproof glass and manufacturing method and application thereof

    CN120191094A